Kinematic viscosity of soybean biodiesel and diesel fossil fuel blends: Estimation from permittivity and temperature - Corach, Julián (2017)
Kinematic viscosity and relative permittivity were determined in blends of soybean biodiesel with diesel fossil fuel in the full range of composition at temperatures between 298 K and 318 K (±0.1 K). The kinematic viscosity as a function of temperature fits very satisfactorily to an Arrhenius dependence at all the compositions. The activation energy of this process depends linearly on blend composition. Also, at constant temperature, the kinematic viscosity increases exponentially with biodiesel content. From the analysis of the experimental data, a model is proposed to estimate the kinematic viscosity of blends of unknown composition as a function of permittivity and temperature. Interestingly, the model parameters depend only on the properties of the pure fuels. The fitting to experimental data is very satisfactory; the RMS uncertainty is lower than 0.02 mm2 s−1.